Evaluación presupuestaria e implementación de una propuesta de mejora en la “Empresa Mancomunada de Movilidad Sustentable de Zamora Chinchipe E.P.” para el periodo 2019 al 2021. - Castillo Pinzón, Alejandro Mauricio (2023)
This investigative work addresses one of the topics of greatest interest for entities and companies that work with financing from public funds; Specifically, it is related to the budget evaluation for the years 2019 to 2021 of the “Empresa Comunidad de Movilidad Sustentable de Zamora Chinchipe E.P.” which has been operating for several years at the service of the Zamora community and which has not been evaluated from the perspective of its budget with which it generates its operations on an annual basis. The general objective that was proposed was to carry out a budgetary evaluation and implementation of an improvement proposal in the "Joint Enterprise of Sustainable Mobility of Zamora Chinchipe E.P." for the period 2019 to 2021, and to comply with this research work, the following specific objectives were established: verify compliance with the annual operating plan, plans, projects and activities of the institution that have been executed according to the assigned budget, with the purpose of indicating the management carried out by its members, measuring the efficiency and effectiveness in the management and execution of the institution's financial resources through the application of budgetary management indicators and preparing a proposal for improvement in the Zamora Chinchipe E.P. for the period 2019 to 2021. In the same way, in its content you can see some strategies that will allow the company under study to improve its activities objectively, since they have been reviewed from other investigations in similar entities and that can significantly favor compliance with their obligations. institutional goals in the short and long term. Among the main results, it can be highlighted that the company has managed to overcome the adversities of the pandemic, with the proper implementation of measures that allow it to continue meeting business objectives at the service of society. Keywords: budget evaluation, projects, efficiency, effectiveness.